Produk Spray Antinyamuk Ramah Lingkungan Berbahan Dasar Tanaman Lidah Buaya dan Sereh Sebagai Upaya Menangkal Penyakit Demam Berdarah - Taupik, Muhammad; Madania, Madania; Mursyidah, Andi; S. Latif, Multiani (State University of Gorontalo, 2023)
Dengue hemorrhagic fever is one of the deadly health problems in Indonesia caused by the bite of the Aedes Aegypti mosquito. In Gorontalo alone, there were 329 cases affected by dengue fever (DHF) in 2019. The first step is socialization of how to prevent the life of mosquito larvae by doing 3M, namely Draining, Closing, and Burying. The second step is to counsel DHF and demonstrate to the public how to make electric herbal mosquito repellent made using the basic ingredients of aloe vera leaves and lemongrass leaves. The product made is very effective for exterminating mosquitoes. When spraying the mosquito-infested room in the first 8 minutes showed that most of the mosquitoes had died. So that the product is considered very effective to eradicate mosquitoes. The hope is that the community is able to maintain the health and cleanliness of the environment and can be independent in making electric herbal mosquito repellent with plant-based ingredients that are easy to find.